Morphological Variations of The Genus Huia Yang,1991 in Region of Java, Kalimantan and Sumatra - Meilinda Rodhiya Idrus; Ahmad Nauval Arroyyan; Saiful Bahri; Amir Hamidy (UIN Sunan Gunung Djati Bandung, 2021)
Huia is a frog belonging to the family Ranidae which has a wide distribution in the world, including in Indonesia. Huia in Indonesia consists of 4 species spread from Sumatra, Java and Kalimantan, namely Huia masonii, Huia cavitympanum, Huia modligianii, and Huia sumatrana. Huia was originally incorporated into the genus Amolops and divided into 3 different sub-genus. The method used was quantitative descriptive as the data obtained in the form of descriptions of the morphometric and meristic characters PAST 3 analyzed software of wet specimens from the Museum Zoologicum Bogoriense. The aims were to determine the morphological variations in Huia characters due to the interesting distribution patterns of species, that were scattered on each island.. The results obtained show that there were morphological variations but have not shown significant grouping with the dominant character of each population of the entire genus Huia in Indonesia.